Lemma 14.33.5. In Situation 14.33.1 the maps

are homotopy equivalences.

Lemma 14.33.5. In Situation 14.33.1 the maps

\[ 1_ i \star \epsilon : i \circ X \to i, \quad \text{and}\quad \epsilon \star 1_ F : X \circ F \to F \]

are homotopy equivalences.

**Proof.**
Denote $\epsilon _ n : X_ n \to X_{-1}$ the components of the augmentation morphism. We observe that $\epsilon _ n = k^{\star (n + 1)}$, the $(n + 1)$-fold $\star $-composition of $k$. Recall that $t : \text{id}_\mathcal {S} \to i \circ F$ is the adjunction map. We have the morphisms

\[ t^{\star (n + 1)} \star 1_ i : i \longrightarrow i \circ (F \circ i)^{\circ (n + 1)} = i \circ X_ n \]

which are right inverse to $1_ i \star \epsilon _ n$ and the morphisms

\[ 1_ F \star t^{\star (n + 1)} : F \longrightarrow (F \circ i)^{\circ (n + 1)} \circ F = X_ n \circ F \]

which are right inverse to $\epsilon _ n \star 1_ F$. These morphisms determine morphisms of simplicial objects $b : i \to i \circ X$ and $c : F \to X \circ F$ (proof omitted). To finish it suffices to construct a homotopy between the morphisms $1, b \circ (1_ i \star \epsilon ) : i \circ X \to i \circ X$ and between the two morphisms $1, c \circ (\epsilon \star 1_ F) : X \circ F \to X \circ F$.

To show the morphisms $b \circ (1_ i \star \epsilon ), 1 : i \circ X \to i \circ X$ are homotopic we have to construct morphisms

\[ h_{n, j} : i \circ X_ n \to i \circ X_ n \]

for $n \geq 0$ and $0 \leq j \leq n + 1$ satisfying the relations described in Lemma 14.26.2. See also Remark 14.26.4. We are forced to set $h_{n, 0} = 1$ and

\[ h_{n , n + 1} = b_ n \circ (1_ i \star \epsilon _ n) = (t^{\star (n + 1)} \star 1_ i) \circ (1_ i \star k^{\star (n + 1)}) \]

Thus a logical choice is

\[ h_{n , j} = (t^{\star (j)} \star 1) \circ (1_ i \star k^{\star (j)} \star 1) \]

Here and in the rest of the proof we drop the subscript from $1$ if it is clear by knowing the source and the target of the morphism what this subscript should be. Writing

\[ i \circ X_ n = i \circ F \circ i \circ \ldots \circ F \circ i \]

we can think of the morphism $h_{n, j}$ as collapsing the first $j$ pairs $(F \circ i)$ to $\text{id}_\mathcal {S}$ using $k^{\star (j)}$, then adding a $\text{id}_\mathcal {S}$ in front and expanding this to $j$ pairs $(i \circ F)$ using $t^{\star (j)}$. We have to prove

We have $d^ n_ m \circ h_{n, j} = h_{n - 1, j - 1} \circ d^ n_ m$ for $j > m$.

We have $d^ n_ m \circ h_{n, j} = h_{n - 1, j} \circ d^ n_ m$ for $j \leq m$.

We have $s^ n_ m \circ h_{n, j} = h_{n + 1, j + 1} \circ s^ n_ m$ for $j > m$.

We have $s^ n_ m \circ h_{n, j} = h_{n + 1, j} \circ s^ n_ m$ for $j \leq m$.

Recall that $d^ n_ m$ is given by applying $k$ to the $(m + 1)$st pair $(F \circ i)$ in the functor $X_ n = (F \circ i)^{\circ (n + 1)}$. Thus it is clear that (2) holds (because $k$ does $\star $-commute with $k$, but not with $t$). Similarly, $s^ n_ m$ is given by applying $1_ F \star t \star i_ i$ to the $(m + 1)$st pair $(F \circ i)$ in $X_ n = (F \circ i)^{\circ (n + 1)}$. Thus it is clear that (4) holds. In the two remaining cases one uses the fact that the compositions in (14.33.2.1) are the identity causes the drop in the index $j$. Some details omitted.

To show the morphisms $1, c \circ (\epsilon \star 1_ F) : X \circ F \to X \circ F$ are homotopic we have to construct morphisms

\[ h_{n, j} : X_ n \circ F \longrightarrow X_ n \circ F \]

for $n \geq 0$ and $0 \leq j \leq n + 1$ satisfying the relations described in Lemma 14.26.2. See also Remark 14.26.4. We are forced to set $h_{n, 0} = 1$ and

\[ h_{n , n + 1} = c_ n \circ (\epsilon _ n \star 1_ F) = (1_ F \star t^{\star (n + 1)}) \circ (k^{\star (n + 1)} \star 1_ F) \]

Thus a logical choice is

\[ h_{n , j} = (1_ F \star t^{\star (j)} \star 1) \circ (k^{\star (j)} \star 1) \]

Here and in the rest of the proof we drop the subscript from $1$ if it is clear by knowing the source and the target of the morphism what this subscript should be. Writing

\[ X_ n \circ F = F \circ i \circ F \circ \ldots \circ i \circ F \]

we can think of the morphism $h_{n, j}$ as collapsing the first $j$ pairs $(F \circ i)$ to $\text{id}_\mathcal {S}$ using $k^{\star (j)}$, then inserting a $\text{id}_\mathcal {S}$ just after the first $F$ and expanding this to $j$ pairs $(i \circ F)$ using $t^{\star (j)}$. We have to prove

We have $d^ n_ m \circ h_{n, j} = h_{n - 1, j - 1} \circ d^ n_ m$ for $j > m$.

We have $d^ n_ m \circ h_{n, j} = h_{n - 1, j} \circ d^ n_ m$ for $j \leq m$.

We have $s^ n_ m \circ h_{n, j} = h_{n + 1, j + 1} \circ s^ n_ m$ for $j > m$.

We have $s^ n_ m \circ h_{n, j} = h_{n + 1, j} \circ s^ n_ m$ for $j \leq m$.

Recall that $d^ n_ m$ is given by applying $k$ to the $(m + 1)$st pair $(F \circ i)$ in the functor $X_ n = (F \circ i)^{\circ (n + 1)}$. Thus it is clear that (2) holds (because $k$ does $\star $-commute with $k$, but not with $t$). Similarly, $s^ n_ m$ is given by applying $1_ F \star t \star i_ i$ to the $(m + 1)$st pair $(F \circ i)$ in $X_ n = (F \circ i)^{\circ (n + 1)}$. Thus it is clear that (4) holds. In the two remaining cases one uses the fact that the compositions in (14.33.2.1) are the identity causes the drop in the index $j$. Some details omitted. $\square$

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like `$\pi$`

). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

## Comments (0)